Comparative Analysis of TCP and UDP Protocol Performance in Sending Text Messages Using Chatting Applications - Wasis Haryono (LPPM Politeknik Aceh Selatan, 2025)
TCP (Transmission Control Protocol) and UDP (User Datagram Protocol) communication protocols are two main protocols used to send data over a computer network. Although both are often used in various network applications, they have different characteristics in terms of reliability, speed, and efficiency. This study aims to conduct a comparative analysis of the performance between TCP and UDP protocols in sending text messages using a chat application. This study was conducted by measuring several main parameters such as message delivery time, reliability level, latency, and throughput. In the TCP protocol, which is connection-oriented, the test results show that text messages are sent with a high level of reliability due to the flow control mechanism, packet sequencing, and retransmission of lost packets. However, this causes higher latency than UDP. In contrast, the UDP protocol, which is connectionless, is able to send messages with lower latency and higher throughput, but does not guarantee message reliability, because there is no retransmission mechanism for lost or damaged packets. The results of this study indicate that the choice between TCP and UDP depends on the specific needs of the application. If the main priority is message delivery reliability, TCP is superior. However, if speed and efficiency are more important, such as in real-time chat applications, UDP can be a better choice. This research is expected to help application developers in choosing the right protocol based on the performance needs of the application used.